2014
DOI: 10.1117/1.jbo.19.2.025001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating HER2 amplification status and acquired drug resistance in breast cancer cells using Raman spectroscopy

Abstract: Abstract. The overexpression of human epidermal growth factor receptor 2 (HER2) is associated with increased breast cancer recurrence and worse prognosis. Effective treatments such as trastuzumab and lapatinib for patients with HER2 overexpression target the blockade of HER2 signaling activities but are often limited by the emergence of acquired drug resistance. This study applied Raman spectroscopy to differentially identify the amplification status of HER2 in cells and to characterize the biochemical composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 48 publications
(43 reference statements)
5
55
0
Order By: Relevance
“…In the future, an exciting possibility is that the successes of Raman based techniques in identifying immune cell types, 36,37 differences between normal, benign and malignant tissues, 38-40 and the discrimination between drug sensitive and drug resistant tumors, 41 may be transferable to coherent Raman imaging by further developing and exploiting the spectroscopic data generated while imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, an exciting possibility is that the successes of Raman based techniques in identifying immune cell types, 36,37 differences between normal, benign and malignant tissues, 38-40 and the discrimination between drug sensitive and drug resistant tumors, 41 may be transferable to coherent Raman imaging by further developing and exploiting the spectroscopic data generated while imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Hartsuiker et al reported variance in lipid levels among breast cancer cell lines with varying HER2 expression levels [13]. Bi et al used Raman spectroscopy to detect lipids in cell lines [48]. In the cell lines treated with lapatinib, a drug-targeting HER2, the lipid levels were increased in the drug-resistant cells.…”
Section: Raman Spectroscopy Of Lipids and Othermentioning
confidence: 99%
“…Studies have shown that patients with HER2-positive breast cancer are at increased risks of recurrence and metastasis [47]. HER2 proto-oncogene expression can be detected by Raman spectra, which have also been used to detect HER2 expression in the BT474 (HER2+), MCF-10A (HER2−), and MCF-10A (HER2+) cell lines [48]. In this study, the application of Raman spectra was first used to characterize the biochemical response of drug resistance and sensitivity to lapatinib, a targeted antitumor agent.…”
Section: Efficacy Of Chemotherapy In Breast Cancer With Ramanmentioning
confidence: 99%
“…27,52 Many studies report the Raman spectroscopic detection of malignant and premalignant tissues in different sites of the body with high sensitivities, has the potential as a new tool in the clinico-oncological practice. 19 The diagnostic potential of Raman spectroscopy has been demonstrated in cancers of various organs including the esophagus, 53 breast, 54 lung, 55 bladder, 56 skin, 57 and prostate. 31 This work described the spectra investigation of single normal and cancerous liver cells using confocal Raman microspectroscopy technology.…”
Section: Discussionmentioning
confidence: 99%